Profiling C4N radicals of astrophysical interest - Bâldea, Ioan (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. Based on a theoretical study of neutral, anion, and cation C4N chains, we suggest that this molecular species can still be observed in space. We analyse the dependence on n of the enthalpies of formation across the CnN family and present possible chemical pathways of C4N production, which are not only exoenergetic but also barrierless. To further assist astronomical observation, we report estimates obtained at the CCSD(T) level of theory for astrophysically and astrochemically relevant properties. These include structural and chemical data, dipole moments, vibrational frequencies, rotational and centrifugal distortion constants as well as electron affinity, ionization potential, and related chemical reactivity indices. Our results indicate that anion chains can be easily detected in space than neutral chains; C4N− possesses a smaller enthalpy of formation and a substantially larger dipole moment than C4N0⁠.